Harmful effects of dietary supplementation of boron on blood parameters of Rainbow Trout (Oncorhynchus mykiss) - ÖZ, M.; KARAȘAHIN, T.; AKSOY, N.H.; INANAN, B.E.; DIKEL, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Even though boron (B), as a trace micronutrient, occurs in natural waters and organisms, its high concentration could cause harmful and even toxic effects for organisms. Lately, studies about positive and negative effects of B on aquatic organisms have been increased with the growing scientific awareness. The aim of the present study was to determine the effects of B-containing feed (0.01%, 0.05%, 0.10%, and 0.20% of B in feed) on hematological and serum biochemical parameters of Rainbow Trout (Oncorhynchus mykiss) compared to the control feed without B. Among the most remarkable results, red blood cell, hemoglobin, and hematocrit values were dramatically decreased in the 0.20 % of B group compared to the control (P<0.05). Also, activities of liver enzymes increased with the increasing B level in the feed. Consequently, B supplementation (> 0.01%) to feed induced negative changes in blood parameters of rainbow trout.